Analysis of p21 expression in cervical carcinoma at a tertiary institution in Ghana: An immunohistochemical study - Babatunde Moses Duduyemi; Ebenezer Kojo Addai; Kweku Bedu-Addo (Nigerian Journal of Medicine, 2023)
Background: Cervical cancer is one of the leading causes of female mortality worldwide. About 85% occur in low-income countries with 13.8% incidence and 14% death in Ghana. p21 has been overexpressed in many cancers. Its overexpression in cervical cancer is linked to tumor growth and a bad prognosis. Aim: The expression profile of p21 in our setting is largely unknown, therefore, the necessity to evaluate p21 expression in cervical cancer. Materials and Methods: A retrospective and descriptive study design was employed to investigate p21 expression in association with demographic and clinicopathological features on formalin-fixed paraffin-embedded cervical cancer tissues. The age, histologic type, and tumor grade of patients were abstracted from the hospital records between January 1, 2015, and December 31, 2016. Tissue microarray of suitable blocks was constructed, and immunohistochemistry was performed. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 26. Results: One hundred and thirty-five cases were used for the study with an age range of 31–115 years and mean age of 58.93 years (standard deviation ± 17.88). Majority of the cases were postmenopausal (40–59 years). Squamous cell carcinoma (SCC) was the most common histological type (96.3%) with the nonkeratinizing variant having the highest frequency (53.1%). Majority of the cases were high grade; Grade 2 (33.3%) and Grade 3 (49.6%). Majority of the cases (66.7%) stained positive for p21 antibody. The associations between p21 and the clinicopathological characteristics were not statistically significant (P > 0.05). p21 was more overexpressed in SCC (64.8%) than adenocarcinoma. Conclusion: An overexpression of p21 in this study suggests that it may contribute to antiapoptosis in cervical cancer leading to tumor progression, aggressive behavior, and poor prognosis.